MANAGEMENT SYSTEM OF IMPROVING THE QUALIFICATIONS OF THE MANAGEMENT STAFF OF THE ORGANIZATION - SHPILEVA, Vira; KOSIIUK, Olena; BILYK, Victoriia (Herald of Khmelnytskyi National University. Economic sciences, 2022)
In the modern development of business technologies, the key resources of any organization, along with informational, financial, and technological ones, are human resources. Enterprises compete, in particular, on the level of professional development of their employees - their knowledge, skills, and abilities. For the most reasonable and effective use of this resource, it is necessary to correctly assess and increase this level. Different systems and methods of personnel evaluation allow to identify and reveal the potential of each employee and direct this potential to the realization of the company's strategic goals. For the successful functioning of any organization, it is necessary to analyze the qualifications, competence and performance of each specific manager. In this regard, the analysis of the competences and effectiveness of the management personnel becomes especially relevant, which will allow to identify the strengths and weaknesses of the management, the reserves of labor productivity growth, determine the optimal numerical composition, and coordinate activities according to needs. For any enterprise or organization, improving the qualifications of personnel is a very important issue, because in order to be a competitive enterprise, to use new technical and technological developments, to improve the quality of products or services, qualified personnel are needed, they constantly improve their qualifications in due to the rapid development of technologies. In addition, the stability and success of the business depends on the qualifications of the staff. Currently, new technologies are constantly being introduced, science is rich in developments, so the main goal of working with personnel is constant training and improvement of staff qualifications. In serious companies, managers have already understood that it is difficult to achieve high-quality solutions in the company, if decisive steps are not taken in the field of personnel training. In connection with this situation, personnel departments primarily direct their efforts to improving the qualifications of management personnel.
Keywords: training; personnel; professional development; management